Athletic career transition : a qualitative inquiry into ex-athletes' experiences of the sports system in Singapore - Suptu, M. Faisal (2012)
Anecdotally, studies on athletic career development and/ or transition revealed that athletes tend to have difficulty immersing their lifestyle into the societal norm after the termination of their athletic career. Based on a cross-cultural study by Alfermann & Stambulova (2002), the phenomenon of athletes coping with this change is no different whether it is voluntary or involuntary termination, and whether the country’s existing sports system does provide assistance in their transitions; within or out of the athletic career. There is a lack of research and empirical evidence to support these claims.